1985
DOI: 10.1002/aic.690310612
|View full text |Cite
|
Sign up to set email alerts
|

Porosity effects on catalytic char oxidation. Part I: A catalyst deposition model

Abstract: Six char samples generated from two coals were impregnated by solutions with different concentrations of NazC03 and/or KzCO3. The catalyst solution penetration was studied, the catalyst uptake was measured, and the effects of impregnation on the char pore structure were determined experimentally. The results indicate that the impregnated catalysts reside only on particle exteriors without significant penetration. The overall rate of reaction is therefore the combination of catalytic reaction on particle exteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Since the isotherms obtained for the impregnated and nonimpregnated samples are almost identical, yielding similar accessible micropore volumes, one can conclude that the catalyst did not block the micropores of these samples to any appreciable extent. Su and Perlmutter (1985a) conducted similar experiments on chars impregnated with sodium and potassium carbonates from aqueous solutions and also found that catalyst addition caused insignificant blockage of the micropores.…”
Section: Catalyst Impregnationmentioning
confidence: 88%
“…Since the isotherms obtained for the impregnated and nonimpregnated samples are almost identical, yielding similar accessible micropore volumes, one can conclude that the catalyst did not block the micropores of these samples to any appreciable extent. Su and Perlmutter (1985a) conducted similar experiments on chars impregnated with sodium and potassium carbonates from aqueous solutions and also found that catalyst addition caused insignificant blockage of the micropores.…”
Section: Catalyst Impregnationmentioning
confidence: 88%